2016
DOI: 10.4209/aaqr.2015.07.0447
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the CCN Activity, BC and UVBC Mass Concentrations of Biomass Burning Aerosols during the 2013 BASELInE Campaign

Abstract: Biomass-burning (BB) aerosols, acting as cloud condensation nuclei (CCN), can influence cloud microphysical and radiative properties. In this study, we present CCN measured near the BB source regions over northern Southeast Asia (Doi Ang Khang, Thailand) and at downwind receptor areas (Lulin Atmospheric Background Station, Taiwan), focusing exclusively on 13-20 March 2013 as part of 2013 spring campaign of the Seven SouthEast Asian Studies (7-SEAS) intensive observation. One of the campaign's objectives is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…These approaches provide useful metrics for constraining the CCN activity in, for example, cloudresolving models, which may help clarify the connections between aerosol hygroscopicity and cloud-radiationprecipitation interactions. During the 2013 BASELInE campaign at DAK, Hsiao et al (2016) reported that the values of κ-parameter were low (0.05-0.1) and correlate well with the amount of particulate organic matter. These observations were comparable with those of κ-parameter estimated from H-TDMA measurements (κ ~0.07-0.08) in the Amazonia (Rissler et al, 2004(Rissler et al, , 2006, as well as consistent with previous studies on water uptake of carbon-dominated aerosols (e.g., Petters et al, 2009;Carrico et al, 2010;Dusek et al, 2011;Engelhart et al, 2012).…”
Section: Hygroscopicity and Aerosol-cloud-radiation Interactionmentioning
confidence: 99%
“…These approaches provide useful metrics for constraining the CCN activity in, for example, cloudresolving models, which may help clarify the connections between aerosol hygroscopicity and cloud-radiationprecipitation interactions. During the 2013 BASELInE campaign at DAK, Hsiao et al (2016) reported that the values of κ-parameter were low (0.05-0.1) and correlate well with the amount of particulate organic matter. These observations were comparable with those of κ-parameter estimated from H-TDMA measurements (κ ~0.07-0.08) in the Amazonia (Rissler et al, 2004(Rissler et al, , 2006, as well as consistent with previous studies on water uptake of carbon-dominated aerosols (e.g., Petters et al, 2009;Carrico et al, 2010;Dusek et al, 2011;Engelhart et al, 2012).…”
Section: Hygroscopicity and Aerosol-cloud-radiation Interactionmentioning
confidence: 99%
“…BVOCs consist primarily of isoprene, monoterpenes, sesquiterpenes and their oxygenated hydrocarbons, such as alcohols, aldehydes and ketones (Ehn et al, 2014;, and account for the majority of the global VOC inventory (Heald et al, 2008;Zhu et al, 2016a, b). However, emission fluxes and oxidation processes of BVOCs show great variation, depending on global warming and other factors such as regional landscape and other pollutants in the ambient air (Ait-Helal et al, 2014;Claeys et al, 2004;Hu and Yu, 2013;Peñuelas and Staudt, 2010). Unlike a potential increase in BVOC-derived organics aerosols in marine atmospheres under global warming, anthropogenic VOCs and carbonaceous particles over the continents have decreased due to effective mitigation of air pollutants over the last few decades Murphy et al, 2011;Sharma et al, 2004;.…”
mentioning
confidence: 99%
“…BB activities in the form of wildland forest fires and agricultural burning are very pronounced in the northern Indochina regions mainly during dry/spring season from late February to mid-April (i.e., Gautam et al, 2013;Hsiao et al, 2016). Aerosol concentrations during this season are typically at peak associated with BB activity and contribute significantly to the regional emissions (Carmichael et al, 2003;Janjai et al, 2009;Streets et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of BB on air quality over Southeast Asia was evaluated within the framework of BASE-ASIA campaign by using chemical transport modelling (Fu et al, 2012;Huang et al, 2013). Moreover, some recent studies also emphasized the BB emissions from Indochina region and explained their impact on regional air quality, atmospheric radiation, hydrological cycle, and climate (e.g., Lin et al, 2013;Tsay et al, 2013;Lin et al, 2014;Tsay et al, 2016) by using in-situ measurements (e.g., Chuang et al, 2013b;Wang et al, 2015;Chuang et al, 2016;Hsiao et al, 2016;Khamkaew et al, 2016;Pantina et al, 2016;Sayer et al, 2016), satellite observations (e.g., Hsu et al, 2003;Huang et al, 2011;Campbell et al, 2013;Lee et al, 2016b), remote sensing Reid et al, 2013), and modeling studies (Fu et al, 2012;Loftus et al, 2016) within the 7-SEAS framework. Wang et al (2015) investigated the presence of strongly absorbing (single-scattering albedo ≈0.88 and absorption angstrom exponent ≈1.5) carbonaceous aerosols within the planetary boundary layer (PBL) over northern Indochina in 2014 spring.…”
Section: Introductionmentioning
confidence: 99%